A study on efficient microbial biodegradation of cellulose based jute composite. Issue 4 (14th December 2019) - Dey, Aparna; Jali, Pallavi; Behera, Ajaya K.; Das, Anath B.; Pradhan, Chinmay
Abstract: Nonbiodegradability and land pollution are the prime factor for choosing biodegradable composite over thermoplastic based composite. As most of the synthetic polymers are nonbiodegradable in nature, hence, their derived composites are losing interest in composite market. In this work, we developed jute fortified bio‐composite utilizing soy milk as the framework material and glutaraldehyde as cross linking component. Mechanical strength of the composites was measured through elasticity (tensile) and transverse rupture (flexural) strength. Characterization of optimized composites by FTIR and FE‐SEM were carried out. Microbial culture system and soil burry methods were used to study biodegradation of the developed composites. Effect of different environmental condition on degradation of composites was evaluated and reported. The most worthwhile significance of these composites is the biodegradation property of its constituents, and can be a superior swap for nonbiodegradable polymer resin based fiber composite. The feasible utilization of this composite is in automobile division, indoor furnishings, cutlery, packaging units, electronic sectors, and so on.